Action research : a guide for the teacher researcher - Mills, Geoffrey E. (Upper Saddle River, N.J. : Merrill/Prentice Hall, 2000)
This text provides a step-by-step, how-to approach of "doing" action research - backed by the most extensive theory and research coverage on the market today. The author guides future and current educators through the action research process with numerous concrete illustrations and a wealth of on-line resources, positioning action research as a fundamental component of teaching alongside curriculum development, assessment, and classroom management."--Jacket
Includes bibliographical references
Keywords: Action research in education -- Handbooks,manuals etc -- Unite State; Teaching -- Handbooks,manuals etc